Guide to Signal Pathways in Immune Cells - Wardle, E. Nigel (Humana Press : Imprint: Humana, 2009)
In Guide to Signal Pathways in Immune Cells, Nigel E. Wardle presents vital information in regards to white cells, like the neutrophils and macrophages, T and B lymphocytes, natural killer cells and mast cells, as they constitute the immune defenses against microbial invaders or tumor cells. In all such cells the necessary information processing for their activities utilizes a network of intracellular signaling pathways. As a guide this book aims to extend understanding of the basic signal transduction pathways that will be suitable for students of immunology or cell biology and for medical personnel at all levels.